Syed Muhammad Naquib al-Attas' Concept of Islamizing Science and its Relevance to Islamic Education - Eka Puspitasari; Anaas Tri Ridlo Dina Yuliana (Universitas Ahmad Dahlan, 2022)
Islamic education has become less moral due to the religious and general science separation. This split in science is blamed on the West's secularization. Adding religious and general science to the Islamic education curriculum can solve this problem. This study aims to determine what Syed Muhammad Naquib Al Attas meant by Islamizing science and how it relates to Islamic education. This article uses qualitative descriptive research that blends history and philosophy. This study used Syed Muhammad Naquib Al Attas's books, other documents, books, and articles. According to Syed Muhammad Naquib al-Attas, the idea of Islamizing science is to free people from magical, mythological, animistic, cultural-national traditions that go against Islam, as well as from the chains of a secular understanding of thought and language and the control of their physical impulses that are often secular and unfair to their nature or soul. Islamic education develops the body, spirit, and mind (Insan Kamil). This research contributes to Islamic education by strengthening the epistemology of the Islamization of science and its relation to Islamic education.